Analyzing Barriers to Transformational Leadership in Education for Sustainability: Case Study at a Cambodian Public University - Sothea Hill; Bunhe Harth; Sambo Ke; Fidero Kuok; Michael Angelo B. Promentilla (Chemical Engineering Transactions)
In the face of the digital revolution and the rapid advancements in science and technology, education for sustainability has become a critical imperative in the 21st century. The transformative power of digital technologies has reshaped society, fostering globalization and disrupting traditional social, economic, and cultural structures. As the world is coping with the challenges posed by climate change, environmental degradation, and social inequalities, it is evident that the success and development of future generations depend on our ability to develop sustainable solutions and adopt responsible practices. Education thus plays a pivotal role in this process, as it empowers individuals with the knowledge, skills, and values necessary to drive positive change and build a more sustainable future. Hence, there is an urgent need to reform educational curricula and learning outcomes to equip students with diverse competencies, behaviors, and character traits necessary for success. Achieving this goal requires teachers to adapt to the fast-paced changes, embrace lifelong learning, and inspire students to surpass their perceived limits while fostering positive attitudes. However, despite the critical role of transformational leadership in this context, teachers face various challenges in motivating and intellectually stimulating their students. This study aims to investigate the barriers to teacher transformational leadership in the context of education for sustainability or sustainable development. Through a case study conducted at a public university in Cambodia, the Decision Making Trial and Evaluation Laboratory (DEMATEL) methodology is employed to map out the causal relationships and elucidate the complex interdependencies between these barriers. The findings underscore the critical importance of anticipating the prominent and influential barrier, which is providing support and involving university administration in implementing transformational leadership. Moreover, policy for the nationwide adoption of transformational leadership must be developed with the support mechanism to ensure that public universities are provided with sufficient resources to foster the culture of transformational leadership. The present insights will contribute to the growing body of knowledge on transformational leadership in education for sustainability. By addressing the identified barriers and promoting effective teacher transformational leadership, universities can better prepare students with the essential 21st-century skills needed to thrive in a carbon-constrained world and contribute to sustainable development.